A novel approach to skull‐base and orbital osteotomies through virtual planning and navigation. (27th August 2018) - Franz, Leonardo; Isola, Miriam; Bagatto, Daniele; Tuniz, Francesco; Robiony, Massimo
Abstract : Objective: Computer‐assisted planning of osteotomy lines, coupled with navigation‐guided performance of planned osteotomies, is a highly innovative approach to skull‐base and orbital surgery. The aim of this pilot study is to provide an assessment of the accuracy of this novel approach in guiding the correct positioning of osteotomy lines in frontal, temporal, and orbital regions, defining the agreement between the spatial position of the planned and performed osteotomies. Methods: Fifteen patients with orbital, frontal sinus, and lateral skull‐base diseases underwent virtual surgical planning. Osteotomies to access the orbit, frontal sinus, and lateral skull base were planned on computer tomography‐based three‐dimensional models. The planned osteotomies were reproduced on the operating field using a navigation system. The positions of the performed and planned osteotomies were compared. The results were described as the mean positional difference between planned and performed osteotomies and as Lin's concordance coefficient, and Bland‐Altman limits of agreement were also defined. Results: The overall mean difference was 0.719 mm (95% confidence interval [CI]: 0.472 to 0.965 mm). Overall, Lin's concordance coefficient was 0.997 (95% CI: 0.996 to 0.998), and overall Bland‐Altman limits of agreement ranged from −1.407 to 2.844 mm. The smallest mean difference (0.587 mm, 95% CI: 0.244 to 0.931 mm) was calculated in the orbit group, whereas the highest mean difference (0.904 mm, 95% CI: 0.428 to 1.379 mm) was described in the lateral skull‐base group. Conclusion: This study's results support the use of this novel planning and navigation protocol for guiding osteotomy in anterior and lateral skull‐base surgery, providing a clinical validation of this technique. Level of Evidence: 4 Laryngoscope, 00:1–9, 2018 Laryngoscope, 129:823–831, 2019